SOCIAL REALITY OF RURAL SOCIETY IN 'H.A.H' DRAMA MANUSCRIPT BY PUTU WIJAYA (REALITAS SOSIAL MASYARAKAT PERKAMPUNGAN DALAM NASKAH DRAMA 'H.A.H' KARYA PUTU WIJAYA) - Ferdian Achsani (UIN Raden Mas Said Surakarta, 2019)
The drama script is a type of prose fiction literature that can not only be enjoyed through pen strokes from writers, but also aims to be performed on stage shows. In drama scripts, the topic or story that is displayed is inseparable from the life of society in general. Through the action of the cast of the cast, it is able to show that the story brought in the script seems to reflect the real life. This study aims to describe the form of reality of social life that occurs in the H.A.H drama by Putu Wijaya. This research is in the form of qualitative descriptive, with the method of analysis analysis through the sociological approach of literature. The source of the data in this study is citation text in the H.A.H drama script by Putu Wijaya, which reflects the reality of social life in the village community. Data collection techniques in this study are document techniques. While the data validity technique used in this study uses source triangulation. Triangulangi source is one of the validity test data that is suitable for use in this study. After analysis, the results of this study show that Putu Wijaya's H.A.H drama script reflects the social life of the community such as: moral degradation, cultural shifts, social conflict, crime. This is due to weak economic conditions, lack of understanding of religious teachings about faith, faith and piety, and lack of education.